Strategi Perencanaan SDM Adaptif dalam Menghadapi Tantangan Budaya dan Hukum pada Perusahaan Multinasional - M. Ifan Asrori; Gladys Maesa Arifin; Gebby Dessinta B; Anita Novianti; Sri Haryani (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Globalization forces multinational companies (MNCs) to manage human resources amidst a diversity of contrasting cultures, laws and policies in each operational country. Rigid and centralized HR planning often creates communication barriers and non-compliance with local regulations, which ultimately reduces organizational performance. This research aims to analyze adaptive HR planning strategies in mitigating cultural and legal challenges in order to increase the effectiveness of company operations in the global market. This research uses a qualitative approach with a library research method. Data was collected through documentation techniques on scientific journal articles, HR management textbooks, and national seminar proceedings for the 2017-2025 period which were then analyzed thematically. The study results show that successful HR planning involves accurate data collection processes, forecasting talent needs, and flexible policy implementation. Adaptive strategies, including cross-cultural training and adjusting compensation systems according to local labor laws, have been proven to minimize communication conflicts and legal risks. Adaptive HR planning is a key element for multinational companies to achieve competitive advantage. The synergy between global quality standards and local wisdom allows the company to maintain stable industrial relations while increasing employee engagement in various operational areas.